SUBACUTE THYROIDITIS AFTER COVID-19 INFECTION - Das, Bhagwan; Tehseen Fatima (Journal of Ayub Medical College Abbottabad, 2021)
Subacute thyroiditis (SAT) is a self-limiting inflammation of the thyroid gland secondary to viral infection of the upper respiratory tract. Clinically it is characterised by fever, neck pain, and deranged thyroid profile. Though SAT historically reported as of post-viral origin, is a quite uncommon extrapulmonary manifestation of COVID-19.